2001
DOI: 10.1002/job.107
|View full text |Cite
|
Sign up to set email alerts
|

A theory‐based measure of conflict management strategies in the workplace

Abstract: SummaryCon¯ict management in¯uences individual wellbeing, group performance and organizational effectiveness. This research examined the psychometric qualities of two versions of the newly developed test for con¯ict handling. The lean version (Study 1 and 2) included problem solving, forcing, yielding and avoiding as distinct con¯ict management strategies, and the expanded version (Study 3) also included compromising. A negotiation study (Study 1) showed substantial convergence between self-reports, opponent-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
348
0
12

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(371 citation statements)
references
References 21 publications
11
348
0
12
Order By: Relevance
“…25 Intraprofessional communication content was guided by a literature review. [26][27][28][29][30][31][32][33][34] Educational experiences used to teach core content were chosen based on those supported in the education literature and included didactic lectures, small group discussions, self-reflection, role play, and simulated and real-life experiences.…”
Section: Methods Phase 1: Faculty Working Group and Needs Assessmentmentioning
confidence: 99%
“…25 Intraprofessional communication content was guided by a literature review. [26][27][28][29][30][31][32][33][34] Educational experiences used to teach core content were chosen based on those supported in the education literature and included didactic lectures, small group discussions, self-reflection, role play, and simulated and real-life experiences.…”
Section: Methods Phase 1: Faculty Working Group and Needs Assessmentmentioning
confidence: 99%
“…We used the "Dutch Test for Conflict Handling" -DUTCH -(De Dreu, Evers, Beersma, Kluwer, & Nauta, 2001) to measure integrative behavior in this study. The items measuring integrative behavior on a 5-point scale anchored at 1 (very low) and 5 (very high) were: "I examined issues until I Conflict Management 16 found a solution that really satisfied me and the other party", "I stood for my own and the other's goals and interests", "I examined ideas from both sides to find a mutually optimal solution", and "I worked out a solution that served my own as well as the other's interests as good as possible".…”
Section: Methods Studymentioning
confidence: 99%
“…Second, our two last studies relied on self-reports of integrative behavior. Although past research has demonstrated that retrospective memories accurately tap into past events in conflict and negotiation research (Beersma & De Dreu, 2002;De Dreu et al, 2001), further research should assess integration by using other methods such as observation, content analyses (e.g., taping the conflict behavior), and asking other individuals involved in the conflict (e.g., the opponent). Related to this, it might also be questioned if some of the studies may suffer from common method biases (especially Study 3), but we believe this to be less of a problem because the inventories we used were quite distinct from each other.…”
Section: Limitations and Further Researchmentioning
confidence: 99%
“…Dreu, Evers, Beersma, Kluwer, & Nauta, 2001). In this regard, it may be valuable to use trained observes to rate trainees in training conditions and give an overall assessment for each trainee on the relevant training elements.…”
Section: Limitations and Further Researchmentioning
confidence: 99%